PARADOKS RUANG TUBUH DALAM PUISI “SAKRAMEN” KARYA JOKO PINURBO: KAJIAN ‘PASCAKOLONIAL TUBUH’ SARA UPSTONE - Dwi Rahariyoso (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This essay explains about postcolonial space body in the poem Sakramen by Joko Pinurbo. In the Upstonepostcolonial context, body is the subject which being ordered the same with home, journey, nation, and city. Body becomesthe last space in colonialism, as a form of power and ownership implementation in supporting the existed systems. Bodybecomes part of colonial absolute definition target, but there is posibility of redefinition continuance. This researchfinds that body construction is found in Sakramen poem paradoxically presents dialiectic between body and soul whichrevolve in the matter of God as body. This construction in the end becomes self-deconstruction for the author whichontologically refers that body (material) is destroyed in impermanence, while spirit (idea) of Christ as God is idealizedin unity. In the end, this condition directs that the ideal contruction is in the spirit world, while in here, (the empirical,physical) is just irony.Keyword: space, post-colonialism, chaos, altenative body, whole budy, paradox, self-deconstruction, irony.